FAKTOR RISIKO KEPADATAN LALAT DAN SANITASI RUMAH DENGAN KEJADIAN DIARE DI KELURAHAN TANJUNG PINANG KOTA JAMBI TAHUN 2017 - Listautin Listautin (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Diarrhea is one of health problem in the world including Indonesia. The Morbidity survey undertaken by Sub-Directorate of diarrhea, Health Department from 2007 to 2010is improved. According to the data gained from Puskesmas in Tanjung Pinang Jambi in 2017, it is found out that 5 different districs in Tanjung Pinang are the district which has the highest rate of diarrhea sufferers. The aim of this study is to find out the risk factors of the flies density and the dwelling sanitation to the occurance of diarrhea in Tanjung Pinang Jambi in 2017. This study is quantitative study by using case control design. The sample of this study is 68 people who consists of 34 samples of case group and 34 samples of control group. This study is analyzed through univariate and bivariate analysis by using chi-square test. The instruments of this study are the reviewed document, ceklist, and the measurement through fly grill. The result of analysis are found out that toilet is the main risk factor for the occurance of diarrhea with odds ratio (OR) value is 3,519. Sewerage (SPAL) is one the risk factor of the diarrhea occurance with odds ratio (OR) value is 3,361. The waste is the other risk factors for the occurance of diarrhea with odds ratio (OR) value is 4,418. The flies density is the protective factor for the diarrhea occurance with odds ratio (OR) value is 0,773.Based on the result of this study, it can be concluded that it is necesarry to do the coorporation across program to optimize the noticing of information to public concerning on the importance of good dwelling sanitation and the low flies density in order to avoid from the occurance of diarrhea.Keyword : Diarrhea, Dwelling Sanitation, Flies Density